Diagnosis of Penicillium marneffei infection by quantitation of urinary antigen by using an enzyme immunoassay - V. Desakorn (2018)
Penicillium marneffei is a major cause of opportunistic infection in patients with AIDS in north and north-eastern Thailand. A method for the quantitation of P. marneffei antigen in urine was developed by using fluorescein isothiocyanate-labelled purified rabbit hyperimmune immunoglobulin G in an enzyme-linked immunosorbent assay. This method was evaluated with 33 patients with culture-proven penicilliosis and 300 controls (52 healthy subjects, 248 hospitalized patients without penicilliosis) from the same area in which penicilliosis is endemic. Urinary antigen was found in all 33 (100%) patients with penicilliosis, with a median titer of 1:20,480. With undiluted samples, 67 (27%) of 248 hospital patients and 3 (6%) of 52 healthy controls were reactive. At a cutoff titer of 1:40, the urine antigen detection assay had a diagnostic sensitivity of 97% and specificity of 98% (positive predictive value, 84%; negative predictive value, 99.7%). This test offers a valuable and rapid method for the diagnosis of penicilliosis in patients with AIDS and could be a useful addition to conventional diagnostic methods in areas in which penicilliosis is endemic.